International transfer pricing in multinational enterprises. (June 2017) - Plesner Rossing, Christian; Cools, Martine; Rohde, Carsten
Highlights: We provide an introduction to international transfer pricing in multinational enterprises. We prepare accounting students for determining arm's-length transfer prices. This paper is positioned in the managerial and tax domain of accounting education. Abstract: Current curricula in management accounting stress the role of transfer pricing as a tool for measuring the performance of responsibility centers and their managers. Recently, however, multinational enterprises (MNEs) have felt increasing pressure to comply with transfer pricing tax regulation. As a result, tax risk management considerations play a key role in the transfer pricing decisions of MNEs today. This case seeks to provide you with examples of the core principles of international transfer pricing, as well as to allow you to discuss international transfer pricing in the context of responsibility accounting. Specifically, the case study is a fictional MNE, allowing you to apply the OECD Guidelines in practice to cross-border transfers within an MNE, and to discuss the implications of tax-based transfer pricing for responsibility accounting. As a basis for working on the case study, the Appendix provides an overview of the 'OECD Transfer Pricing Guidelines for Multinational Enterprises and Tax Administrations' (OECD, 2010), hereafter OECD Guidelines, upon which most transfer pricing regulations worldwide are based. It includes an introduction to the arm's length principle, OECD-accepted transfer pricing methods, and comparability analysis procedures for identifying comparable transactions between independent parties. The case study assumes that you are familiar with responsibility accounting and transfer pricing as discussed by standard management accounting textbooks.